Altered gene expression in human placenta after suspected preterm labour. (July 2017) - Oros, D.; Strunk, M.; Breton, P.; Paules, C.; Benito, R.; Moreno, E.; Garcés, M.; Godino, J.; Schoorlemmer, J.
Abstract: Introduction: Suspected preterm labour occurs in around 9% of pregnancies. However, almost two-thirds of women admitted for threatened preterm labour ultimately deliver at term and are considered risk-free for fetal development. Methods: We examined placental and umbilical cord blood samples from preterm or term deliveries after threatened preterm labour as well as term deliveries without threatened preterm labour. We quantitatively analysed the mRNA expression of inflammatory markers (IL6, IFNγ, and TNFα) and modulators of angiogenesis (FGF2, PGF, VEGFA, VEGFB, and VEGFR1). Results: A total of 132 deliveries were analysed. Preterm delivery and term delivery after suspected preterm labour groups showed similar increases in TNFα expression compared with the term delivery control group in umbilical cord blood samples. Placental samples from preterm and term deliveries after suspected preterm labour exhibited significantly increased expression of TNFα and IL6 and decreased expression of IFNγ. Suspected preterm labour was also associated with altered expression of angiogenic factors, although not all differences reached statistical significance. Discussion: We found gene expression patterns indicative of inflammation in human placentas after suspected preterm labour regardless of whether the deliveries occurred preterm or at term. Similarly, a trend towards altered expression of angiogeneic factors was not limited to preterm birth. These findings suggest that the biological mechanisms underlying threatened preterm labour affect pregnancies independently of gestational age at birth. Highlights: False preterm labour is considered to pose no risks to fetal development. Suspected preterm labour induces inflammatory gene expression in human placentas. Suspected preterm labour alters angiogenic gene expression in human placentas. Biological mechanisms of suspected preterm labour affect term-born pregnancies.